2010
DOI: 10.1111/j.1462-2920.2010.02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Halophilic archaea in the human intestinal mucosa

Abstract: The human gastrointestinal tract microbiota, despite its key roles in health and disease, remains a diverse, variable and poorly understood entity. Current surveys reveal a multitude of undefined bacterial taxa and a low diversity of methanogenic archaea. In an analysis of the microbiota in colonic mucosal biopsies from patients with inflammatory bowel disease we found 16S rDNA sequences representing a phylogenetically rich diversity of halophilic archaea from the Halobacteriaceae (haloarchaea), including nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 57 publications
4
107
0
4
Order By: Relevance
“…Archaeal diversity (16S rRNA gene TRFs) was greater than MA diversity (mcrA TRFs). This observation indicates significant colonization by non-MA, which is in accordance with previous detection of non-MA from colonic mucosa (Oxley et al, 2010). Alternatively, it is possible that MA harboring the mrtA functional gene, such as Msp.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Archaeal diversity (16S rRNA gene TRFs) was greater than MA diversity (mcrA TRFs). This observation indicates significant colonization by non-MA, which is in accordance with previous detection of non-MA from colonic mucosa (Oxley et al, 2010). Alternatively, it is possible that MA harboring the mrtA functional gene, such as Msp.…”
Section: Discussionsupporting
confidence: 78%
“…Relatively limited MA diversity has been detected, with only Methanobrevibacter smithii and Methanosphaera stadtmanae cultured from stool (Miller et al, 1982;Miller and Wolin, 1985) and also predominant in molecular surveys (Eckburg et al, 2005;Zhang et al, 2009). More recently, Oxley et al (2010) reported the presence of Mb. smithii, Mb.…”
Section: Introductionmentioning
confidence: 99%
“…In another study the microbiota in colonic mucosal biopsies from patients with inflammatory bowel disease, 16S rDNA sequences representing a phylogenetically rich diversity of halophilic archaea from the Halobacteriaceae were determined. The study revealed a multitude of undefined bacterial taxa and a low diversity of methanogenic archaea (Oxley et al, 2010). Representatives of Archaea, the third domain of life, were generally thought to be limited to environmental extremes of the earth.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Like Bacteria, Archaea are commonly mesophilic, and some members are known to be closely associated with eukaryotic hosts, including humans. For instance, high numbers of methane-producing Archaea (methanogens) have been detected in the gastrointestinal tract, vagina, and oral cavity (Belay et al, 1990;Vianna et al, 2006) and recently non-methanogenic Archaea including members of the Crenarchaeota, Thermococcales, Thermoplasmatales and Halobacteriaceae, have been detected in human faeces (Oxley et al, 2010). They are now recognized as a component of human microbiota and it is subjects of debate wheather archaea are cause of any disease in human.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation